Local community’s perception of the appropriateness and success of tourism development models in lower Kinabatangan region, Sabah, East Malaysia - Ghasemi, Moslem (2015)
The growth of mass tourism has led to the problems of environmental, social, and cultural degradation. In an effort to address these problems, alternative forms of tourism have been developed. This has resulted in a rapidly developing tourism industry that has already gone through different models such as Pro-Poor Tourism (PPT), Community-Based Tourism (CBT), and Community Benefit Tourism Initiatives (CBTIs). On top of that, it is found that the opinions of local communities on tourism development within their areas vary significantly depending on certain variables such as community’s expectations and perception of their benefits. Therefore, this study aims to investigate the appropriateness and success level of tourism models developed in rural areas from a local community's point of view via a comparative study of CBT and CBTI in 2 villages of Lower Kinabatangan region. The first step is to determine the local community’s choice of appropriate tourism paradigm in their regions and their reasons behind it and the second is to evaluate the success level of these two oft-debated tourism paradigms from a local community’s perspective. Both quantitative and qualitative research methods were employed to achieve the research goal. A decision making model based on 42 research variables as its input data was created using the Analytic Network Process (ANP) method that employed the Interpretive Structural Modeling (ISM) technique. The decision making model used questionnaires which are designed based on the model’s regulations to determine the choices of the local communities and local operators in regard to CBT and CBTI. Furthermore, a questionnaire was used to determine the local communities’ satisfaction of tourism success level. The results revealed that both local communities from the 2 villages and local operators from Batu Putih village preferred CBT as the appropriate tourism model for their region while local operators from Sukau village preferred CBTI as the appropriate tourism model in their region. The results also showed that local communities view CBT to be more successful than CBTI.